Bounded Rationality and Repeated Network Formation - Nicolas Querou; Sylvain Beal (Fondazione Eni Enrico Mattei (FEEM), 2006)
We define a finite-horizon repeated network formation game with consent, and study the differences induced by different levels of individual rationality. We prove that perfectly rational players will remain unconnected at the equilibrium, while nonempty equilibrium networks may form when, following Neyman (1985), players are assumed to behave as finite automata. We define two types of equilibria, namely the Repeated Nash Network (RNN), in which the same network forms at each period, and the Repeated Nash Equilibrium (RNE), in which different networks may form. We state a sufficient condition under which a given network may be implemented as a RNN. Then, we provide structural properties of RNE. For instance, players may form totally different networks at each period, or the networks within a given RNE may exhibit a total order relationship. Finally we investigate the question of efficiency for both Bentham and Pareto criteria.
Keywords: C72; 330; Repeated Network Formation Game; Two-sided Link Formation Costs; Bounded Rationality; Automata; Beschränkte Rationalität; Netzwerk; Spieltheorie; Theorie